Zero Trust Service Function Chaining - Bradatsch, Leonard; Kargl, Frank; Miroshkin, Oleksandr (Electronic Communications of the EASST, 2021)
In this paper, we address the inefficient handling of traditional security functions in Zero Trust (ZT) networks. For this reason, we propose a novel network security concept that combines the ideas of ZT and Service Function Chaining (SFC). This allows us to efficiently decide which security functions to apply to which packets and when.